Keefektifan Model Learning Cycle 7E Berbantuan Flipchart Terhadap Sikap Sosial Siswa Kelas III SDN Langensari 03 - Yuniana, Within Prayogi; Purwanti, Kartika Yuni (Universitas PGRI Semarang, 2022)
This study aims to determine the effectiveness of the Flipchart-assisted Learning Cycle 7E learning model on students' social attitudes. The design of this research is Quasi Experimental Design, Pretest-Posttest Control Group Design. Data collection techniques using questionnaires, observations, and interviews. Data were analyzed by descriptive analysis, Independent Sample T-Test, Simple Linear Regression Test, and Paired Sample T-Test. The results showed: (1) There were differences in the use of the Flipchart-assisted Learning Cycle 7E model on students' social attitudes. This is evidenced by the results of the Independent Sample T-Test with a significance value of less than 0.05 (0.005 0.05). (2) There is an effect of using the Flipchart-assisted Learning Cycle 7E model on students' social attitudes. This is evidenced by the results of the Simple Linear Regression Test with a significance value of less than 0.05 (0.005 0.05). (3) There is an increase in the use of the Flipchart-assisted Learning Cycle 7E model on students' social attitudes. This is evidenced by the results of the Paired Sample T-Test with a significance value of less than 0.05 (0.000 0.05). So it can be concluded that the Learning Cycle 7E model assisted by Flipchart is effective in improving students' social attitudes.